EEG IMAGING APPLICATION ON POSITIVE EMOTION OF AFFECTIVE NEUROSCIENCE - Helman, A.A.; Mohd Arhan, A.S.; Amin, M.K.M.; Muzahidul Islam, A.K.M.; Mikami, O. (Journal of Advanced Manufacturing Technology (JAMT), 2019)
This research paper explored the brain electrical activities of human positive emotions through Electroencephalography (EEG) device. Modern day EEG device has made it possible to record and analyze the electrophysiological pattern of the brainwaves. Brain reactions to certain situation and environment affect human physical body and produce physiological or emotions effects. However, the correlation of human emotion and its electrophysiological is still poorly understood. Although many scientific research has been carried out, it is still remain a big challenge as the physiology and psychology of human and living being cannot be quantify directly. The previous study investigated the positive emotion of the affective neuroscience. Despite being important for many functioning in humans, it is far less researched compared to negative emotions. This study elaborates its findings by investigating the relation between positive emotion with EEG frequency and its cognitive relation to the brain lobes. Human subjects participated for this experiment and were assigned to watch several stimulus videos while wearing the Emotiv Epoch to record their brainwaves. The results show that different positive emotions generate different spatial patterns. The spatial patterns and frequency bands for joy, inspiration and serenity particularly shows distinguishable difference compared to other positive emotions.